Exploring non-native English-speaking teachers' cognitions about corrective feedback in teaching English oral communication. (December 2015) - Rahimi, Muhammad; Zhang, Lawrence Jun
Abstract: Exploring teachers' cognitions is a significant endeavour, as teachers' cognitions inform their classroom practice, and, in turn, their cognitions are influenced by their teaching experiences. This study explored the differences between novice and experienced non-native English-speaking teachers' cognitions about corrective feedback (CF) in teaching English oral communication. Data were collected from 20 novice and 20 experienced teachers through a questionnaire and follow-up interviews. Results show statistically significant differences between the two groups. Teachers' personal experiences influenced their cognitions about the necessity of CF and the effectiveness of different CF types and timing. Interview data show teachers' teaching experiences raise their awareness of the role of mediating factors, namely learner factors, error frequency, types, and severity, target form difficulty, instructional focus, and task types in their cognitions about the necessity, timing, and types of CF. In contrast, novice teachers, partially due to their insufficient teaching experiences, had rigid cognitions about CF. Novice teachers attributed their cognitions to their personal language learning experiences. As a pedagogical implication, we recommend that student teachers be provided with opportunities for acquiring theoretical understanding about CF and translating it into classroom practice.